1997
DOI: 10.1111/j.1445-5994.1997.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity to porcine factor VIII of factor VIII inhibitors in patients with haemophilia in Australia and New Zealand

Abstract: Many patients in Australia and New Zealand with inhibitors to human factor VIII presently show a low or absent level of cross-reactivity to porcine factor VIII. These may respond to treatment with this concentrate at least in the short term. There remains a group of patients with high cross-reactivity who will respond only to recombinant factor VIIa or prothrombin complex concentrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Many studies and reviews have reported on the treatments and efficacy of various treatments for AH over the years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The large prospective study by UKHCDO 2 is the largest and most recent prospective study and serves as a new benchmark for management of this rare acquired bleeding disorder. The European Acquired Hemophilia Registry has also collected >500 patients in their database, and we will have more clinical data available on this rare condition soon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies and reviews have reported on the treatments and efficacy of various treatments for AH over the years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The large prospective study by UKHCDO 2 is the largest and most recent prospective study and serves as a new benchmark for management of this rare acquired bleeding disorder. The European Acquired Hemophilia Registry has also collected >500 patients in their database, and we will have more clinical data available on this rare condition soon.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There have been many published studies and reviews on the management of AH. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The strategy to manage AH is essentially twofold after the correct diagnosis is made: (1) to start antibody eradication or immune suppression promptly, and (2) to achieve hemostasis when there is clinically significant bleeding, particularly life-or limb-threatening bleeding.…”
Section: Abstract: Acquired Hemophilia Rituximab Recombinant Activamentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of haemorrhage is by human or porcine derived factor VIII concentrate or recombinant factor VIIa. Porcine factor VIII is effective in most cases because the level of inhibitor against it is usually low 6–8 . If the level of inhibitor to human factor VIII is low, high doses of human factor VIII may be sufficient 7 …”
Section: Patient Characteristics Associated Conditions and Coagulatimentioning
confidence: 99%
“…Porcine factor VIII is effective in most cases because the level of inhibitor against it is usually low. [6][7][8] If the level of inhibitor to human factor VIII is low, high doses of human factor VIII may be sufficient. 7 Due to the morbidity and mortality associated with this condition, treatment aimed at elimination of the autoantibody is important.…”
mentioning
confidence: 99%